PEMODELAN SISTEM ANTRIAN DENGAN MENGGUNAKAN SIMULASI - Firman Ardiansyah Ekoanindiyo (Jurnal Ilmiah Dinamika Teknik, 2011)
Simulation as mode to yield the condition of from situation with model for study to test or training, and others. According to system law viewed as orders corps limiting either by itself system capacities and also that system place environment reside in, Model defined as a logical description about how system work or its components react. Queue arise because of requirement of service will exceed ability (service capacity) or service facility, so that consumer of facility which arrive cannot immediately get service caused workload of service. Many matter, additional service facility can be given to lessen queue or to prevent incidence of queue. However expense of because giving service of addition, will generate reduction of advantage possible reach under store; level able to be accepted. Keywords: Simulation, System, Model, Queue